Inclusive education in rural schools of Ukraine or how to ensure quality inclusive education in rural schools in Ukraine? - Olena Budnyk; Sergiy Sydoriv; Lesia Serman; Olena Lushchynska; Tetianа Tsehelnyk; Lyudmila Matsuk (Universidade Federal do Norte do Tocantins, 2022)
The aim of the paper is to reveal the challenges of implementation of inclusive education in typical rural schools of Ukraine. The authors performed empirical research to identify attitudes of rural school teachers towards inclusive education as well as their understanding of existing barriers and priorities to improve the quality of educational services for students with special educational needs (SEN). To achieve the aim of the research, the following methods have been used: reviewing of psychological and pedagogical literature, questionnaire surveys, quantitative and qualitative analysis of the obtained data. The outlined problem has been theoretically analyzed and the peculiarities and difficulties of teaching students with special educational needs in rural areas have been substantiated. The paper describes survey responses of teachers involved in the inclusive process in rural schools. 192 representatives of different age categories and regions of Ukraine participated in this empirical study. The paper explores questions of effective management of rural schools, professional cooperation in a team of psychological and pedagogical support of students with special educational needs, promotion of inclusive practices via information and communication technologies (ICT) and STEAM-laboratories, cooperation within local communities, introduction of universal design for learning and others. Prospects for the development of rural inclusive schools in current conditions of digitalization of education also have been identified.